Surface or full cementation of the tibial component in total knee arthroplasty: a matched-pair analysis of mid- to long-term results - Schlegel, Ulf J.; Bruckner, Thomas; Schneider, M.; Parsch, D.; Geiger, F.; Breusch, S. J. (Archives of orthopaedic and trauma surgery, 2015)
INTRODUCTION: Despite the clinical success of cemented TKA, aseptic loosening of the tibial component remains a potential long-term complication. Considering the constantly growing revision burden, there is a need for clarification regarding controversial views on primary fixation techniques. In this retrospective analysis, surface (SC) or full cementation (FC) of tibial components was compared in a matched-pair and long-term setting. - METHODS: Matching pairs were identified in a patient series from 1989 to 1994. Hence, 25 primary TKA (SC) were compared to 42 TKA (FC). The study population included 34 patients with rheumatoid arthritis. Patients were matched in a 1:1.7 fashion according to age, gender and initial diagnosis. Outcome was assessed by multiple clinical parameters, detailed radiographic evaluation and survivorship analysis. - RESULTS: Clinical follow-up (FU) was at 10.3 years (range 1.5-15.6) for the SC and 12 years (range 0.2-16.2) for the FC group. Survivorship at 10 years was 100 % for the surface cemented trays and 93.3 % (95 % CI 80.5-100) for the fully cemented implants considering aseptic loosening as endpoint (p = 0.3918). Improvement of the AKS Score was greater in the SC group (p = 0.044) and patients in this group were more satisfied (p = 0.013). For any other clinical parameter, no difference could be observed (p > 0.05). - CONCLUSION: Results of this study showed no statistically significant difference regarding long-term survivorship for the two cementing techniques. This finding questions the claimed advantage of full cementation for tibial components. The presented data do not support the concern that surface cementation results in insufficient fixation in patients with rheumatoid arthritis.